Modeling the Impact of Cotton Production on Economic Development in Benin: A Technological Innovation Perspective - Chabi Simin Najib, Dafia; Fei, Chen; Dilanchiev, Azer; Romaric, Samson (Frontiers in Environmental Science, 2022)
This research provides an in-depth understanding of cotton production in Benin. The analysis explored the effects of cotton production on economic growth using a VECM. The findings highlighted that there is a strong and positive connection between cotton export and economic growth and a long-term relation between the human capital and the economic growth in Benin. A rapid human capital development will increase the quality of the employment generation, and the country's economy will adjust upward. Furthermore, a short-run coefficient unveils feedback necessary in the relative level of investment to bring back the economic growth to equilibrium. Before the VECM, a descriptive analysis was conducted. Both approaches were run on a time series database collated over 60 years from national and international organizations, including the World Bank, the United States Department of Agriculture, and the national accounts. From these findings discussed in this paper, the Government of Benin is commended for diversifying the production of cotton through a town target policy.